Sustainability of yoga practice among the victims of natural disaster in Kerala: A follow- up study - D, Mathew (International Journal of Psychosocial Rehabilitation, 2020)
Natural disasters take a huge toll on mankind affecting their health and economical status. Nearly 8.5 million people across 141 countries has been affected by disasters in 2018.1 Psychological problems such as depression, anxiety, post-traumatic stress disorder (PTSD), and other unspecified types of stress are commonly seen among the people who are exposed to extreme traumatic events like natural disasters.2,3 Studies suggests resilience as one of the key factor to recover from psychological trauma owing to natural disasters which helps the victims to revive positive life.4 Yoga is regarded as a tool to mitigate mental health issues arising due to natural disasters.